2007
DOI: 10.1016/j.str.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Partial Agonists Activate PPARγ Using a Helix 12 Independent Mechanism

Abstract: Binding to helix 12 of the ligand-binding domain of PPARgamma is required for full agonist activity. Previously, the degree of stabilization of the activation function 2 (AF-2) surface was thought to correlate with the degree of agonism and transactivation. To examine this mechanism, we probed structural dynamics of PPARgamma with agonists that induced graded transcriptional responses. Here we present crystal structures and amide H/D exchange (HDX) kinetics for six of these complexes. Amide HDX revealed each l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
421
2
17

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(487 citation statements)
references
References 49 publications
47
421
2
17
Order By: Relevance
“…In fact, it is a partial agonist of PPARc with a weaker transcriptional activity [52][53][54]. This relationship is in agreement with our previous findings regarding two enantiomeric ureidofibrate derivatives complexed with PPARc, showing partial and full agonism, respectively, toward this nuclear receptor [52].…”
Section: Docking Of Compounds 2a and 2b Into Pparc Binding Pocketsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, it is a partial agonist of PPARc with a weaker transcriptional activity [52][53][54]. This relationship is in agreement with our previous findings regarding two enantiomeric ureidofibrate derivatives complexed with PPARc, showing partial and full agonism, respectively, toward this nuclear receptor [52].…”
Section: Docking Of Compounds 2a and 2b Into Pparc Binding Pocketsupporting
confidence: 92%
“…9D). Interestingly, this compound makes no direct contacts with H12 residues, a hallmark of traditional TZDs, but preferentially stabilizes H3 through closer hydrophobic contacts or H-bonds made with residues of this helix (S289, F282, Q283 and Q286), likely affecting coactivator recruitment and transactivation potential [52][53][54]. Consistently, compound 2B may be considered a PPARc partial agonist and indeed displays a weaker transactivation profile than 2A (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Structural characterization of indeglitazar bound to the 3 PPARs revealed that, for PPAR␦ and PPAR␥, a single water molecule was recruited into the signaling interface from ligand to receptor. Interestingly, the 4 aromatic residues of the signaling tetrad in the PPAR␥-indeglitazar co-structure overlap closely with the same set of residues observed in the complex of PPAR␥ with another partial agonist, MRL20 (25). However, whereas MRL20 shows a response of Ϸ80% relative to rosiglitazone, indeglitazar is more substantively reduced to Ϸ45%.…”
Section: Discussionsupporting
confidence: 53%
“…Instead, partial-agonists display hydrophobic interaction in branch II or III, leading to the stabilization of H3 and the b-sheet region rather than H12. 38 A hydrogen bond with Ser342 at the border of two branches is observed for some partial agonists to reinforce this hydrophobic interaction. This H12-independent activation mechanism is characteristic of partial agonists.…”
Section: Mechanism Of Ppar Gamma Activation By Telmisartanmentioning
confidence: 93%
“…These include multiple intermolecular hydrogen bonds between carboxylic acid, or its bioisostere, and amino-acid residues Ser289, His323, His449 and Tyr473, as well as intramolecular hydrogen bonds among these four residues and Tyr327. 38 In addition, a certain level of occupation in branches II or III is required to increase affinity.…”
Section: Mechanism Of Ppar Gamma Activation By Telmisartanmentioning
confidence: 99%